How Important Is U.S. Location for Research in Science? - Kahn, Shulamit; MacGarvie, Megan J. (The Review of Economics and Statistics, 2016)
This paper asks whether being located outside the United States lowers research productivity in a data set of foreign-born, U.S.-educated scientists. Instrumenting location with visa status that requires return to home countries, we find a large negative relationship between non-U.S. location and research output for countries with low income per capita but none for countries with high income per capita. This suggests that a scientist exogenously located in a country at the top of the income distribution can expect to be as productive in research as he or she would be in the United States.